Meningkatkan Kualitas Pelayanan Publik di DKI Jakarta melalui Aplikasi JAKI: Pendekatan New Public Service dan Inovasi Teknologi - Zaidatul Ulya; Bintoro Wardiyanto; Erna Setijaningrum (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The JAKI (Jakarta Kini) application, launched by the DKI Jakarta Provincial Government as part of the Jakarta Smart City initiative, has become an innovative solution in improving public service quality in Jakarta. This application integrates various public services into a single digital platform, enabling citizens to access services more easily, quickly, and transparently. The aim of this study is to analyze the effectiveness and efficiency of the JAKI application in public service delivery, as well as to evaluate whether its implementation aligns with the principles of New Public Service and the concept of Open Innovation. This research adopts a qualitative descriptive approach by gathering data from various sources such as articles, government reports, and related literature reviews. The findings show that the JAKI application has successfully enhanced accessibility, citizen participation, and transparency in public services, but it still faces several challenges, such as the digital divide, technical issues, and uneven digital literacy across different societal groups. Nevertheless, this application has introduced the concept of Open Innovation by involving the private sector and the community in service development, as well as improving accountability through direct reporting features like JakLapor.